Studi Faktor-Faktor Penyebab Keterlambatan Pengadaan Tanah Dan Pengaruhnya Terhadap Waktu Pelaksanaan Proyek Pembangunan Bendungan Bagong Paket 1 Di Kabupaten Trenggalek (MYC) - Dimas Ade Hermawan; Taufik Dwi Laksono; Faisol AM (JOURNAL SAINS STUDENT RESEARCH, 2023)
Development problems in Indonesia are divided into two large parts, namely the problem of development objects and the problem of subjects who will carry out development. The problems that originate from the subject of development are procurement. The problem of providing land is very vulnerable in its handling, because it concerns the lives of many people. If we look at the government's need for land for development purposes, it can be understood that the available state land is very limited, therefore the only way that can be taken is by liberate land belonging to the community, whether it has been authorized by rights based on Customary Law or other rights. The method used for data processing in this research is a mixed method (mixed methodology), namely a combination of qualitative and quantitative methods. Quantitative methods were used to describe technical data at the research location. At the stage of explaining land acquisition issues, a qualitative approach was taken because it tends to be very subjective. This research was conducted by applying SIDLACOM. Based on the research results, in the Bagong dam construction project there were several problems in the land acquisition process, including social problems, technical problems, financial problems and administrative problems. In the Bagong Dam construction project, social problems and administrative problems were the main keys in causing delays in land acquisition, thereby causing delays in the construction project. The solution for handling delays in land acquisition is that first, accurate research needs to be carried out to determine the value of compensation by considering the location of the land, criteria for land and buildings, land use, quality of buildings, and the economic conditions of the affected communities. Second, improve coordination between related parties. Third, carry out appropriate and repeated socialization. And fourth, conduct good negotiations.